The Economics of Price Scissors: Comment - Carter, Michael R. (American Economic Review, 1986)
In a recent issue of this Review, (1984) Raaj Kumar Sah and Joseph Stiglitz model the impact of shifts in the agriculture-industry terms of trade on industrial accumulation and social welfare.' The intersectoral terms of trade, they note, was a key issue in the Soviet industrialization debate of the 1920's, and continues to be an important issue in contemporary less developed countries. One seemingly surprising implication of the Sah-Stiglitz model is that a shift in the terms of trade against agriculture increases industrial accumulation despite (or rather, because of ) a normal agricultural supply response. In their model, a price-induced decline in marketed agricultural surplus requires depression of industrial wages in order to reequilibrate urban food demand with supply at the lower relative food price. The income and substitution effects of these wage and price changes lower urban consumption demand for industrial goods. Together with agriculture's reduced purchasing power, this lower urban demand leads to the price scissors-induced increase in investable surplus out of industrial production. Thus emerges the strong Sah-Stiglitz result, which they label Preobrazhensky's First Proposition, that the more elastic is agricultural supply response, the more wages must be depressed in equilibrium, and the more effectively plice scissors work to increase accumulation (see their equation (15)). Apparently, the traditional preoccupation with agricultural supply response, including Preobrazhensky's,2 is wrong-headed and backwards. But it is argued here that this result obtains only under rather special labor supply and investable surplus assumptions which conform to neither the constraints of the Soviet industrialization debate, nor to most contemporary less developed countries.3